Smart Shear-Thinning Hydrogels as Injectable Drug Delivery Systems - Samimi Gharaie, Sadaf (Polymers (Basel), 2018)
In this study, we fabricated and characterized a smart shear-thinning hydrogel composed of gelatin and laponite for localized drug delivery. We added chitosan (Chi) and poly N-isopropylacrylamide-co-Acrylic acid (PNIPAM) particles to the shear-thinning gel to render it pH-responsive. The effects of total solid weight and the percentage of laponite in a solid mass on the rheological behavior and mechanical properties were investigated to obtain the optimum formulation. The nanocomposite gel and particles were characterized using Fourier-transform infrared spectroscopy (FTIR), scanning electron microscope (SEM), zeta potential, and dynamic light scattering techniques. Finally, release related experiment including degradability, swelling and Rhodamine B (Rd) release at various pH were performed. The results suggest that incorporation of silicate nanoplatelets in the gelatin led to the formation of the tunable porous composite, with a microstructure that was affected by introducing particles. Besides, the optimum formulation possessed shear-thinning properties with modified rheological and mechanical properties which preserved its mechanical properties while incubated in physiological conditions. The release related experiments showed that the shear-thinning materials offer pH-sensitive behavior so that the highest swelling ratio, degradation rate, and Rd release were obtained at pH 9.18. Therefore, this nanocomposite gel can be potentially used to develop pH-sensitive systems.